Will the global HIV response fail gay and bisexual men and other men who have sex with men? - George Ayala; Glenn‐Milo Santos (Journal of the International AIDS Society, 2016)
Introduction Gay and bisexual men and other men who have sex with men are among the small number of groups for whom HIV remains uncontrolled worldwide. Although there have been recent and notable decreases in HIV incidence across several countries, prevalence and incidence is consistently higher or rising among men who have sex with men when compared with other groups. Methods In 2014, MSMGF (the Global Forum on MSM & HIV) conducted its third biennial Global Men's Health and Rights Study, an international, multilingual, web‐based cross‐sectional survey of men who have sex with men recruited through online convenience sampling. We tested hypothesized correlates (selected a priori) of successfully achieving each step along the HIV prevention and treatment continuum by fitting separate generalized estimating equation models adjusted for clustering by country in multivariate analyses. All models controlled for ability to meet basic financial needs, age, healthcare coverage, having a regular provider, region and country‐level income. Results Higher provider discrimination and sexual stigma were associated with lower odds of perceived access to services, service utilization and virologic suppression. Conversely, accessing services from community‐based organizations focused on lesbian, gay, bisexual and transgender people; greater engagement in gay community; and comfort with healthcare providers were associated with higher odds of achieving steps along the prevention and treatment continuum. Conclusions To meet accelerated global HIV targets, global leaders must adopt a differentiated and bolder response, in keeping with current epidemiologic trends and community‐based research. The HIV‐related needs of gay and bisexual men and other men who have sex with men must be addressed openly, quickly and with sufficient resources to support evidence‐based, community‐led and human rights‐affirming interventions at scale.